Comparison of Efficacy and Safety Between Standard, Accelerated Epithelium-Off and Transepithelial Corneal Collagen Crosslinking in Pediatric Keratoconus: A Meta-Analysis - Li, Yuanjun; Lu, Ying; Du, Kaixuan; Yin, Yewei; Hu, Tu; Fu, Yanyan; Xiang, Aiqun; Fu, Qiuman; Wu, Xiaoying; Wen, Dan (Frontiers in Medicine, 2022)
Purpose: To compare the efficacy of standard epithelium-off (SCXL), accelerated epithelium-off (ACXL), and transepithelial cross-linking (TECXL) for pediatric keratoconus. Methods: A literature search on the efficacy of SCXL, ACXL, and TECXL (including accelerated TECXL (A-TECXL)) for keratoconus patients younger than 18 years was conducted using PubMed, Cochrane Library, ClinicalTrials.gov, and EMBASE up to 2021. Primary outcomes were changes in uncorrected visual acuity (UCVA) and maximum keratometry (Kmax) after CXL. Secondary outcomes were changes in best-corrected visual acuity (BCVA), mean refractive spherical equivalent (MRSE), and central corneal thickness (CCT). Estimations were analyzed by weighted mean difference (WMD) and 95% confidence interval (95% CI). Results: Eleven identified studies enrolled 888 eyes (SCXL: 407 eyes; ACXL: 297 eyes; TECXL: 28 eyes; A-TECXL: 156 eyes). For pediatric keratoconus, except for a significant greater improvement in BCVA at 24-month follow-up in SCXL (WMD = -0.08, 95%CI: -0.14 to -0.01, P = 0.03, I2 = 71%), no significant difference was observed in other outcomes between the SCXL and ACXL group. SCXL seems to provide greater changes in UCVA (WMD = -0.24, 95%CI: -0.34 to -0.13, P <0.00001, I2 = 89%), BCVA (WMD = -0.09, 95%CI: -0.15 to -0.04, P =0.0008, I2 = 94%), and Kmax (WMD = -1.93, 95%CI: -3.02 to -0.85, P =0.0005, I2 = 0%) than A-TECXL, with higher incidence of adverse events. Conclusion: For pediatric keratoconus, both SCXL and ACXL appear to be comparable on the efficacy in visual effects and keratometric outcomes; SCXL seems to provide greater changes in visual and pachymetric outcomes than A-TECXL.